Cross-cultural adaptation of the Hospital Survey on Patient Safety Culture questionnaire to the Cuban context - Rosa María Blanco Quintana; Yuliett Mora Pérez; Tania Solange Bosi de Souza Magnago; Liuva Miriela Navarro Martiatu; Yoslaidy Guerra Insua; Zenia Tamara Sánchez García (Medisur)
Foundation: patient safety culture is the product of values, beliefs, attitudes, perceptions, norms, procedures, competencies and patterns of individual and group behavior, which determines the commitment of a health organization to the management of patient safety. Objective: to carry out cultural adaptation of the Hospital Survey on Patient Safety Culture instrument to the Cuban context. Methods: descriptive, cross-sectional study, carried out from January to March 2023, with workers from the Frank País International Orthopedic Scientific Complex, which consisted of four phases: first phase: instrument qualitative analysis, second phase: scale selection, third phase: pilot test with 17 workers, fourth phase: second pilot test with 30 workers. Results: in the qualitative analysis with experts, words are eliminated, added and changed from the instrument; in the first test, 73.6% answered them on scales one and two of incomprehensible and poorly understood and 2.3% did not answer some of dimensions. In the second pilot, 78.2% answered on the scales of understandable and completely understandable in the cultural adaptation of the instrument. The final questionnaire has 42 items grouped into 12 dimensions and these are in three sections, just like the original. Conclusions: the questionnaire has a comprehensible and relevant structure to measure the perception of the patient safety culture at the Frank País International Orthopedic Scientific Complex.